Pelaksanaan Amalan Chaplaincy Muslim di Hospital Mesra Ibadah (HMI) - Surina Mohamad Shafi; Mohd Zulkifli Awang; Nurul Aisyah Amir Ramli; Izzati Aminah Subhan; Ishak Mas’ud (USIM Press, 2024)
Vol. 33 No. S5 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences